A perfect day for digging - Best, Cari; Davenier, Christine (Las Vegas, NV : Two Lions, 2014)
While Nell and her dog, Rusty, dig in their yard, Norman, the boy next door who hates getting dirty, looks on until he finally decides to join in the fun.
Keywords: Neighbors -- Fiction; Friendship -- Fiction; Cleanliness -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Cleanliness -- Fiction; Dogs -- Fiction